2003
DOI: 10.1093/bja/aeg046
|View full text |Cite
|
Sign up to set email alerts
|

Predictive performance of computer-controlled infusion of remifentanil during propofol/remifentanil anaesthesia

Abstract: Remifentanil can be administered by TCI with acceptable bias and inaccuracy. The three pharmacokinetic parameter sets described by Egan and colleagues resulted in the least bias and best accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(44 citation statements)
references
References 22 publications
0
42
0
2
Order By: Relevance
“…Indeed, it is widely accepted that the Minto pharmacokinetic model can predict plasma concentrations of remifentanil. Mertens and colleagues [27] showed that the median performance error (MDPE) and median absolute performance error (MDAPE) of TCI remifentanil were -15 and 20 % for Minto pharmacokinetic parameter, which indicated the predictive bias and inaccuracy of Minto pharmacokinetic parameter were clinically acceptable. Another limitation is that DEX was not target-controlled infused to maintain the same plasma concentration at the moment of skin incision.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is widely accepted that the Minto pharmacokinetic model can predict plasma concentrations of remifentanil. Mertens and colleagues [27] showed that the median performance error (MDPE) and median absolute performance error (MDAPE) of TCI remifentanil were -15 and 20 % for Minto pharmacokinetic parameter, which indicated the predictive bias and inaccuracy of Minto pharmacokinetic parameter were clinically acceptable. Another limitation is that DEX was not target-controlled infused to maintain the same plasma concentration at the moment of skin incision.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent reflex stimulation of the efferent limb results in coughing [4]. The antitussive effect of opioids generally is centrally mediated by brainstem opioid receptors [4,24], and remifentanil administration via TCI may maintain a predictable Ce with an acceptable level of bias and inaccuracy [25,26]. Therefore, the authors attempted to determine the effective remifentanil Ce for abolishing cough using the TCI in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These two intravenous medications are optimal for delivery via TCI because of their short context-sensitive half-lives. (17) When administered with a plasma target model, TCI could lead to more stable haemodynamic parameters. (18) Currently, most patients undergoing bronchoscopy receive MS with a different regimen than the one used in the present study.…”
Section: Discussionmentioning
confidence: 99%